Introducción en Guayaquil del yogurt artesanal hecho de arazá con stevia, con fines medicinales - Loma Iturralde, David Antenor (2009)
This article contains the production and marketing of artisanal yogurt made with fruit is also called Araza and sweetened with a plant called Stevia, which help people suffering from diabetes and hypertension which is intended as a contribution to society with a new trend of yogurt. We will create loyalty among consumers, giving a product of good taste and quality. It develops a marketing plan for greater market share. Furthermore, we analyze a technical study seeking the feasibility of production and marketing of yogurt. To determine the feasibility of the project required financial analysis, covering all components of cash flow required for their implementation, for example, the costs and benefits of each period, projected to the year 5, then, measure based on these flows Internal Rate of Return (IRR) and the calculation of Net Present Value (NPV). Finally we conclude with the sensitivity analysis of the project as determined by the tools of Crystal Ball. The project is profitable yogurt him financially which is highly beneficial for the company.